Association of Metabolic Syndrome with Migraine: A Case-Control Study (Bangladesh Journal of Neuroscience, 2018)
Background: Migraine is a disabling primary headache disorder and metabolic syndrome is a major escalating public-health challenge worldwide. They share some common pathophysiology. But till date, their relationship is obscure.Methods: This study was conducted in headache clinic and inpatient-outpatient department of Neurology and Biochemistry laboratory of BSMMU, from June 2017 to February 2019. In these age-sex matched case control study, 30 migraine patient and equal number non migraine volunteer were taken according to inclusion exclusion criteria. Waist circumference (WC), blood pressure (BP), fasting plasma glucose (FPG), serum triglyceride (TG) and high density lipoprotein cholesterol (HDL-C) were measured among all.Results: In this case control study, 24 women and 6 men were taken in both case and control groups, with mean age (±SD) of 32 (±7.77) and 30 (±8.46) years respectively. Metabolic syndrome was significantly higher among migraineurs (36.7% in case and 13.3% in control group respectively, p=0.037). Patient with metabolic syndrome had 3.763 times more chance of having migraine then person without metabolic syndrome [p=0.037, OR=3.763, 95% C.I. (1.038-13.646)].Conclusion: There is an association between metabolic syndrome and migraine.Bangladesh Journal of Neuroscience 2018; Vol. 34 (1): 17-24